Implementation of Specialized Pharmaceutical Care Hospital Outpatient Clinics in a Hospital Pharmacy Department - Luis Margusino-Framiñán; Purificación Cid-Silva; Cristina Martínez-Roca; Marta García-Queiruga; Elena Fernández-Gabriel; María Mateos-Salvador; María Teresa Rabuñal-Álvarez; María Isaura Pedreira-Vázquez; Isabel Martín-Herranz (Elsevier, 2017)
Objective: To describe the organization of patient care into Specialized Pharmaceutical Care Hospital Outpatient Clinics in a Hospital Pharmacy Department, to evaluate their healthcare quality, and the quality perceived by outpatients. Method: A retrospective observational study in a High-Level Hospital Pharmacy Department during three periods (years 2010, 2013 and 2016); description of the organization at the levels of structure, human resources, material resources and working procedures; evaluation of healthcare quality through the analysis of three variables in terms of procedure: prior appointment compliance, waiting time and documentation of pharmaceutical care; evaluation of quality perceived by outpatients through a satisfaction survey; comparative statistical analysis of means (Student's t) and proportions (Pearson's chi square) Results: Fifteen (15) specialized outpatient clinics were opened and managed by 18 pharmacists; between the initial and final periods of the study (2010 vs. 2016), the compliance with previous appointments was of 61.3% vs. 88.8% (p <0001), waiting time was 27.6±12.1 vs. 12.1±5.4 minutes (p <0.0001), documentation of pharmaceutical care in the clinical record was of 2.3% vs. 9.81% (p <0.0001), and the overall satisfaction perceived by the patients was 6.63±2.36 vs. p.16±1.27 (p <0.01). Conclusions: The model of Specialized Pharmaceutical Care Hospital Outpatient Clinics exposed, focused on the patient and with continuity of care, has improved the quality of care and the quality perceived by the patients and it´s in optimal conditions to investigate its contribution on health outcomes and on the health system through a better quality, safety and efficiency of pharmacotherapy